Study of factors controlling the amount of 0.01 M CaCl2 extractable Norg fraction - Szabó, Emese; Loch, Jakab (Acta Agraria Debreceniensis, 2018)
The use of new methods describing the “readily available” nutrient content of the soil is spreading on a global scale. The 0.01 M CaCl2 extractant is a dilute salt solution in which the easily soluble inorganic (nitrate-N and ammonium-N) and organic N fractions, P, K and micronutrients are also measurable. The 0.01 M CaCl2 has been tested in the University of Debrecen, Institute of Agricultural Chemistry and Soil Sciences since the 90’s. The results of the researches related to organic N fraction, performed in the last decades, and the results of the present study (originating from the long-term experiment of Karcag, 2007–2009) can be concluded as follows: The measurement of easily soluble and oxidizable organic nitrogen (Norg), besides inorganic fractions, could improve the nutrient management. The amount of the Norg fraction is determined by the soil conditions, therefore it is considered to be a site-specific parameter. Management practices and cropyear affect the amount of Norg as well. The present research confirmed that, the effect of fertilization on the amount of Norg can be explained by the changing of the yield (related to total biomass production), while the effect of cropyear is related to the differences in mineralization circumstances and yield as well. The measurement of the Norg fraction is increases the accuracy of N-supply, therefore it could prevent the environmentally harmful excess N application as well.